Prevalence of multidrug-resistant organisms in hospitalized pediatric refugees in an university children’s hospital in Germany 2015-2016 - Tenenbaum, Tobias; Becker, Klaus-Peter; Lange, Bettina; Weichert, Stefan; Schroten, Horst (Infection control and hospital epidemiology, 2016)
OBJECTIVE - To determine the prevalence of multidrug-resistant organisms (MDROs) colonizing in pediatric refugees admitted to a University Children Hospital in Germany. - - - DESIGN - Retrospective observational study. - - - SETTING - General pediatric and pediatric surgery units. - - - PATIENTS - In Germany, recommendations for MDRO screening of pediatric refugees were recently published. According to these and institutional recommendations, all hospitalized pediatric refugees were screened for MDROs between October 2015 and March 2016. - - - METHODS - Using electronic surveillance data, we performed a chart review to identify the prevalence of MDROs among and the clinical diagnoses of pediatric refugees. - - - RESULTS - Among 325 patients hospitalized for various causes, most frequently gastroenteritis (30.9%), MDROs were detected in 33.8%. Most of these patients were colonized with multidrug-resistant Gram-negative (MRGN) bacteria (113 isolates), mostly 2MRGN/ESBL (87 isolates); some patients were colonized with methicillin-resistant Staphylococcus aureus (MRSA, 22 isolates); and 1 patient was colonized with vancomycin-resistant enterococci (VRE). Among 110 refugee patients, we detected single colonization with an MDRO in 84 patients (76.4%), co-colonization with 2 pathogens in 23 patients (20.9%), and triple colonization in 3 patients (2.7%). However, infections with MDROs occurred in only 3.6% of pediatric refugees. The peak of positive MDRO screening results in 2015 correlated with an increased hospitalization rate. - - - CONCLUSION - Implementation of infection control measures among pediatric refugees is challenging. Due to the high frequency of MDROs in these patients, current screening, isolation, and treatment strategies may have to be adapted. - - Infect Control Hosp Epidemiol 2016;1-5
Gesehen am 25.06.2019